Diaportones A–C: Three New Metabolites From Endophytic Fungus Diaporthe foeniculina BZM-15 - Kang, Fenghua; Lu, Xiuxiang; Zhang, Sha; Chen, Dekun; Kuang, Min; Peng, Weiwei; Tan, Jianbing; Xu, Kangping; Zou, Zhenxing; Tan, Haibo (Frontiers in Chemistry, 2021)
Phytochemical investigation of Diaporthe foeniculina BZM-15 led to one new γ-butyrolactone derivative, diaportone A (1), one cyclopentenone derivative, diaportone B (3), and one monoterpene derivative, diaportone C (5), along with six known compounds (2, 4, and 6–9). Their structures as well as the absolute configurations were characterized by means of NMR, HRESIMS, and ECD spectroscopy and quantum chemistry calculation, respectively. Furthermore, all compounds were evaluated for their cytotoxic activity and antibacterial activity, and compounds 7 and 8 displayed significant antiproliferative effects on three human cancer cell lines (SF-268, MCF-7, and HepG2) with IC50 values ranging from 3.6 to 15.8 μM.